Histone deacetylase 4 shapes neuronal morphology via a mechanism involving regulation of expression of vascular endothelial growth factor D - Litke, Christian; Bading, Hilmar; Mauceri, Daniela (The journal of biological chemistry, 2018)
Nucleo-cytoplasmic shuttling of class IIa histone deacetylases (i.e. HDAC4, -5, -7, and -9) is a synaptic activity- and nuclear calcium-dependent mechanism important for epigenetic regulation of signal-regulated gene expression in hippocampal neurons. HDAC4 in particular has been linked to the regulation of genes important for both synaptic structure and plasticity. Here, using a constitutively nuclear-localized, dominant-active variant of HDAC4 (HDAC4 3SA), we demonstrate that HDAC4 accumulation in the nucleus severely reduces both the length and complexity of dendrites of cultured mature hippocampal neurons, but does not affect the number of dendritic spines. This phenomenon appeared to be specific to HDAC4, as increasing the expression of HDAC3 or HDAC11, belonging to class I and class IV HDACs, respectively, did not alter dendritic architecture. We also show that HDAC4 3SA decreases the expression of vascular endothelial growth factor D (VEGFD), a key protein required for the maintenance of dendritic arbors. The expression of other members of the VEGF family and their receptors was not affected by the nuclear accumulation of HDAC4. VEGFD overexpression or administration of recombinant VEGFD, but not VEGFC, the closest VEGFD homologue, rescued the impaired dendritic architecture caused by the nuclear-localized HDAC4 variant. These results identify HDAC4 as an epigenetic regulator of neuronal morphology that controls dendritic arborization via the expression of VEGFD.
Gesehen am 26.02.2020